The everyday project manager : a primer for learning the principles of successful project management - Nicholls, Jeremy (Boca Raton, FL : Routledge, 2021)
The best organizations, and even the best departments within organizations, have a roadmap: a clear vision of where they would like to be and the means by which they will get there. This roadmap drives the everyday activity of the company as well as any change it makes both internally and externally. And it is what drives projects. In fact, it is arguable that success in business is almost wholly reliant on an ability to implement change effectively - whether it is a computer system that gives you the edge on your competitor, bringing a new product to market, adopting new ways of working, or completely redefining the approach your company takes. Success and survival in business relies on change and the way that business implements change is through projects. Therefore, if you work in the world of business, sooner or later the chances are that you will be involved in a project, as a stakeholder, advisor, sponsor or possibly running it - as the project manager. In The Everyday Project Manager, author and project management expert Jeremy Nicholls shares the key attributes and skills of successful project management and describes the practical skills that will enhance project delivery regardless of your level of experience. The skills and concepts detailed in this book can be easily understood and implemented. They are "everyday" (that is, commonplace) skills, but they are skills and the concepts that the best project managers use every day. Each chapter details the concepts, practices, and tools that readers will use to build their proficiency in every phase of delivering a project efficiently and effectively.
Introduction Part One: What Is The Everyday Project Manager? Introduction Part Two: Some Project Management Definitions Phase 1: Project Start-up Chapter 1: What are we doing here?: The Vision, Benefits and Objectives Chapter 2: The trade-off: We offer three kinds of service Chapter 3: Project scope: Defining the requirements Chapter 4: Roles and Responsibilities: I'm putting the team back together for one last job Phase 2: Design Chapter 5: The best laid plans: Planning & estimating your project Chapter 6: How much?!: Budgeting and Cost Management Chapter 7: Control mechanisms: Setting up your Project Governance Phase 3: Build & Execute Chapter 8: Hell is other people: Managing the team Phase 4: Project Closure & Lessons Learned Chapter 9: Managing uncertainty: a brief introduction to risk management Chapter 10: In extremis: how to manage difficult projects Appendices In summary: delivering a project in three pages Key information for Every (Everyday) Project
"A Productivity Press book."
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Project management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Production & Operations Management